Alloy material for inductor, preparation method of alloy material and inductor

By generating a Cr2O3 oxide layer on the surface of FeSiCr alloy particles, forming an inductive alloy material for core-shell structure, and controlling the proportional relationship between the median particle size and the thickness of the oxide layer, the shortcomings of existing materials in insulation voltage resistance and magnetic permeability balance are solved, and a higher comprehensive inductance performance is achieved.

CN119772169AActive Publication Date: 2025-04-08DONGGUAN SUNLORD ELECTRONICS CO LTD

Patent Information

Application Number
CN202411982336.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing alloy materials for inductance have shortcomings in insulation voltage resistance and magnetic permeability balance, and it is difficult to achieve the performance of the theoretical value of the material.

Method used

The inductive alloy material for inductors is used to form a core-shell structure by using FeSiCr alloy particles as the core by generating a Cr2O3 oxide layer on its surface, and the proportional relationship between the median particle size D50 of the alloy material particles and the thickness T of the Cr2O3 layer is satisfied within a specific range.

Benefits of technology

By optimizing the structure and process of the alloy material, the magnetic permeability of the material is improved to be close to the theoretical value, and the insulation voltage resistance is improved at the same time, achieving a better balance between magnetic permeability and insulation voltage withstand voltage, and improving the overall performance of the inductor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119772169A_ABST
    Figure CN119772169A_ABST
Patent Text Reader

Abstract

The invention discloses an alloy material for an inductor, a preparation method of the alloy material and the inductor, particles of the alloy material for the inductor are of a core-shell structure, a shell is attached to the outer surface of a core, the core is FeSiCr alloy particles, the shell is a Cr2O3 layer, and the FeSiCr alloy particles and the Cr2O3 layer are arranged on the outer surface of the core. The median particle diameter D50 of particles of the alloy material and the thickness T of the Cr2O3 layer meet the following relation: when D50 is greater than or equal to 3 microns and less than 5 microns, the percentage of T in D50 is in the range of [0.98%, 2.49%]; when D50 is more than or equal to 5 microns and less than 10 microns, the percentage of T in D50 is within the range of (2.49%, 3.95%); when D50 is more than or equal to 10 microns and less than 25 microns, the percentage of T in D50 is within the range of (3.95%, 8.56%). According to the invention, the magnetic conductivity and the insulation and voltage resistance of the alloy material are well balanced, and the comprehensive performance of the inductor is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of inductor components, and in particular to an alloy material for inductor, a preparation method thereof and an inductor. Background Art

[0002] At present, the performance of alloy materials used for power inductors is often difficult to reach the theoretical value of the material. In the prior art, the insulation coating of most alloy materials is mainly carried out in the following ways: 1. Coating a layer of organic resin material on the surface of the alloy particles to form an insulating layer. However, the thermal stability of the resin material is poor, and it is easy to decompose or soften at high temperature, which affects the insulation effect of the magnetic core; in addition, the increase in the thickness of the resin material will lead to a decrease in the inductance performance of the magnetic core, and the uneven coating will affect the close stacking between the particles, resulting in a decrease in performance. 2. Generating an inorganic oxide film (such as SiO2, Al2O3, etc.) on the surface of the alloy particles by chemical or physical methods to enhance the insulation. This process is relatively complicated and easily leads to increased costs. 3. After coating the alloy powders of different particles, they are mixed and sintered to form a multi-layer structure to achieve the insulation effect. This method is prone to cracking or shedding of the oxide layer during the sintering process, which affects the insulation effect, and the coating of the multi-layer structure increases the difficulty and cost of sintering. The existing alloy materials for inductors have the problem of insufficient balance between insulation withstand voltage and magnetic permeability.

[0003] It should be noted that the information disclosed in the above background technology section is only used for understanding the background of the present application, and therefore may include information that does not constitute prior art known to ordinary technicians in the field. Summary of the invention

[0004] In order to make up for the deficiencies of the prior art, the present invention provides an alloy material for an inductor, a preparation method thereof, and an inductor.

[0005] The present invention adopts the following technical solution:

[0006] In a first aspect, an alloy material for inductance is provided, wherein particles of the alloy material are of a core-shell structure, the shell is attached to the outer surface of the core, the core is a FeSiCr alloy particle, and the shell is a Cr2O3 layer, wherein the median particle size D50 of the particles of the alloy material and the thickness T of the Cr2O3 layer satisfy the following relationship: when 3μm≤D50<5μm, the percentage of T in D50 is in the range of [0.98%, 2.49%]; when 5μm≤D50<10μm, the percentage of T in D50 is in the range of (2.49%, 3.95%]; when 10μm≤D50<25μm, the percentage of T in D50 is in the range of (3.95%, 8.56%]).

[0007] In a second aspect, a method for preparing the alloy material for inductance according to the first aspect is provided, which comprises the following steps:

[0008] (1) Using FeSiCr alloy powder as raw material, cleaning the surface of the powder to remove the naturally oxidized part of the powder surface;

[0009] (2) In an inert atmosphere containing oxygen, the FeSiCr alloy powder cleaned in step (1) is sintered to form a Cr2O3 layer on the surface of the particles, thereby obtaining the inductor alloy material, wherein the median particle size D50 of the inductor alloy material is in the range of 3 to 25 μm.

[0010] In a third aspect, an inductor is provided, which includes the alloy material for inductor described in the first aspect.

[0011] The present invention has the following beneficial effects: the present invention solves the problem of insufficient balance between insulation withstand voltage and magnetic permeability in the existing alloy materials for inductance, and in the alloy material for inductance provided, the magnetic permeability of the alloy material is closer to the theoretical value of the material by controlling the proportional relationship between the median particle size D50 of the alloy material and the thickness T of the Cr2O3 layer, and at the same time has excellent insulation withstand voltage. The present invention achieves a better balance between the magnetic permeability and insulation withstand voltage of the alloy material, and improves the comprehensive performance of the inductor. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 is a scanning electron microscope image of the alloy material in Example 1 of the present invention;

[0013] Figure 2 3 is a scanning electron microscope image of the alloy material in Example 2 of the present invention. DETAILED DESCRIPTION

[0014] The following is a detailed description of the embodiments of the present invention. It should be emphasized that the following description is only exemplary and is not intended to limit the scope and application of the present invention. In the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other.

[0015] A specific embodiment of the present invention provides an alloy material for inductance, wherein the particles of the alloy material are of a core-shell structure, the shell is attached to the outer surface of the core, the core is a FeSiCr alloy particle, and the shell is a Cr2O3 layer, wherein the median particle size D50 of the particles of the alloy material and the thickness T of the Cr2O3 layer satisfy the following relationship: when 3μm≤D50<5μm, the percentage of T in D50 is in the range of [0.98%, 2.49%]; when 5μm≤D50<10μm, the percentage of T in D50 is in the range of (2.49%, 3.95%]; when 10μm≤D50<25μm, the percentage of T in D50 is in the range of (3.95%, 8.56%]).

[0016] In some embodiments, when the median particle size D50 of the alloy material particles is 3.04 μm, the percentage of T in D50 is in the range of 0.99% to 1.64%; when the median particle size D50 of the alloy material particles is 5.14 μm, the percentage of T in D50 is in the range of 2.53% to 2.92%; when the median particle size D50 of the alloy material particles is 10.50 μm, the percentage of T in D50 is in the range of 4.29% to 5.24%; when the median particle size D50 of the alloy material particles is 21.7 μm, the percentage of T in D50 is in the range of 7.14% to 8.53%.

[0017] The specific embodiment of the present invention also provides a method for preparing the alloy material for inductance, which comprises the following steps:

[0018] (1) Using FeSiCr alloy powder as raw material, cleaning the surface of the powder to remove the naturally oxidized part of the powder surface;

[0019] (2) In an inert atmosphere containing oxygen, the FeSiCr alloy powder cleaned in step (1) is sintered to form a Cr2O3 layer on the surface of the particles, thereby obtaining the inductor alloy material, wherein the median particle size D50 of the inductor alloy material is in the range of 3 to 25 μm.

[0020] By directly sintering the FeSiCr alloy powder to form a dense Cr2O3 layer on its surface, the insulation performance of the material can be effectively improved, and it has the following advantages: the Cr2O3 oxide layer formed by sintering is dense and uniform, and has high thermal stability; directly forming an oxide layer on the surface of the particles avoids the structural complexity of traditional coatings, makes the particles stacked more closely, forms a uniform stacking structure, and also reduces air gaps; compared with other coating methods, the process flow of the method of the present invention is simpler, which helps to reduce production costs and improve the stability of the production process. In addition, the thickness of the Cr2O3 layer is controlled during sintering, thereby controlling the proportional relationship between the median particle size D50 of the particles of the alloy material and the thickness T of the Cr2O3 layer to satisfy the following Relationship: when 3μm≤D50<5μm, the percentage of T in D50 is in the range of [0.98%, 2.49%]; when 5μm≤D50<10μm, the percentage of T in D50 is in the range of (2.49%, 3.95%]; when 10μm≤D50<25μm, the percentage of T in D50 is in the range of (3.95%, 8.56%], so that the electric field distribution inside the alloy material is more uniform, and a better balance is achieved between the magnetic permeability and the insulation withstand voltage, thereby improving the comprehensive performance of the inductor. If the proportional relationship between the median particle size D50 of the alloy material particles and the thickness T of the Cr2O3 layer is not within the above range, it is difficult to simultaneously improve the insulation withstand voltage performance and the magnetic permeability of the inductor, which will affect the performance of the power inductor.

[0021] It is worth noting that during the sintering process, due to uneven powder distribution or local temperature differences, the Cr2O3 layer may not be fully generated on the surface of some alloy particles. This local unevenness is inevitable at the microscopic scale. Considering the errors in the actual process, it is expected that no more than 10wt% of the alloy particles will have this situation. This deviation belongs to the common error range in the manufacturing process and will not significantly affect the overall performance of the material.

[0022] In some embodiments, the cleaning in step (1) refers to cleaning the surface of the powder with an inert gas.

[0023] In some embodiments, in step (2), the thickness of the Cr2O3 layer is controlled by controlling at least one of the sintering temperature, the sintering time and the oxygen concentration in the inert atmosphere, thereby controlling the proportional relationship between the median particle size D50 of the particles of the alloy material and the thickness T of the Cr2O3 layer.

[0024] In some embodiments, in step (2), the sintering temperature is 750-880° C. (preferably 800-880° C.), the sintering time is 0.5-3 h, and the oxygen concentration in the inert atmosphere is 21 vol% to 50 vol%.

[0025] In some embodiments, the inert atmosphere containing oxygen contains oxygen and further contains at least one of nitrogen and argon.

[0026] In some embodiments, the Cr content in the FeSiCr alloy powder of step (1) is ≥ 2 wt %; preferably, in step (1), the Cr content in the FeSiCr alloy powder is ≥ 2 wt % and ≤ 4 wt %.

[0027] In some embodiments, the FeSiCr alloy powder of step (1) contains 91.5wt%-93.5wt% Fe, 4.5wt% Si and 2.0wt%-4.0wt% Cr.

[0028] In some embodiments, in step (1), the FeSiCr alloy powder contains 91.5wt% Fe, 4.5wt% Si and 4.0wt% Cr; or the FeSiCr alloy powder contains 92.5wt% Fe, 4.5wt% Si and 3.0wt% Cr; or the FeSiCr alloy powder contains 93.5wt% Fe, 4.5wt% Si and 4.0wt% Cr.

[0029] In some embodiments, the particle size distribution D50 of the FeSiCr alloy powder in step (1) is in the range of 2 to 20 μm.

[0030] A specific embodiment of the present invention further provides an inductor, which includes the alloy material for inductor.

[0031] The specific embodiments of the present invention are further described below.

[0032] Example 1

[0033] The preparation method of the alloy material comprises the following steps:

[0034] 1. Select FeSiCr alloy powder with a particle size distribution (median particle size) D'50 = 3μm (the mass percentage of each component is as follows: Fe is 91.5%, Si is 4.5%, Cr is 4.0%) to ensure uniform distribution of powder particles and reduce the influence of impurities of fine particles. Use inert gas to clean the surface of the powder to remove the naturally oxidized part of the powder surface to ensure the uniformity and consistency of the Cr2O3 layer generated by oxidation.

[0035] 2. Under nitrogen atmosphere protection, the cleaned FeSiCr alloy powder was heated to 800°C at a heating rate of 5°C / min in an environment with an oxygen volume fraction of 30 vol%, kept at this temperature for 1 hour (i.e., the sintering and oxidation time was 1 hour), and naturally cooled to room temperature to obtain an alloy material with a median particle size D50 of 3.04 μm and a Cr2O3 layer thickness T of 30-50 nm. Figure 1 As shown, after scanning electron microscope analysis and measurement, the thickness of the Cr2O3 layer is uniform and flat, with a thickness of 30-50nm, and the percentage of the thickness T of the Cr2O3 layer to D50 is in the range of 0.99% to 1.64%.

[0036] 3. Add an appropriate amount of adhesive to the alloy material obtained in step 2, load it into a mold of 8×5×2mm, and apply a pressure of 900MPa to press the powder into shape. Load the pressed magnetic ring into the sintering mold, keep it sealed, pass inert gas, and perform sintering. The sintering temperature is controlled at 850℃ for 9 hours. This sintering temperature can ensure that the Cr2O3 insulating layer between the particles will not be damaged during the sintering process, and it helps to form a stable interface bond between the particles, making the magnetic core more compact.

[0037] 4. The performance of the formed magnetic ring was tested, and the test results are shown in Table 1.

[0038] Comparative Example 1

[0039] The difference from Example 1 is that the sintering oxidation time in step 2 is 20 minutes. After scanning electron microscope analysis and measurement, the thickness of the surface Cr2O3 layer of the alloy material obtained in Comparative Example 1 is 10-20nm, the median particle size D50 of the alloy material particles is 3.01μm, and the percentage of the thickness T of the Cr2O3 layer to D50 is in the range of 0.33% to 0.66%. The other steps are the same as Example 1. The performance test of the magnetic ring formed by the alloy material of Comparative Example 1 is carried out, and the test results are shown in Table 1.

[0040] Comparative Example 2

[0041] The difference from Example 1 is that the sintering oxidation time in step 2 is 5 hours. After scanning electron microscope analysis and measurement, the thickness of the Cr2O3 layer on the surface of the alloy material obtained in Comparative Example 2 is 100-120nm, the median particle size D50 of the alloy material particles is 3.11μm, and the percentage of the thickness T of the Cr2O3 layer to D50 is in the range of 3.22% to 3.86%. The other steps are the same as those in Example 1. The performance test of the magnetic ring formed by the alloy material of Comparative Example 2 is carried out, and the test results are shown in Table 1.

[0042] Table 1:

[0043] project Magnetic Permeability Insulation(MΩ) Withstand voltage(V) Comparative Example 1 118 20 146 Example 1 110 1800 1401 Comparative Example 2 87 2000 1787

[0044] As can be seen from Table 1, the magnetic permeability of the sample of Example 1 is 110, the insulation is 1800MΩ, the withstand voltage is 1401V, and the magnetic permeability is close to 92% of the theoretical value (the theoretical value of the magnetic permeability of the material in this example is 120). The magnetic permeability of the sample of Example 1 is closer to the theoretical value under the condition of meeting the insulation withstand voltage requirements, while the insulation withstand voltage of the sample of Comparative Example 1 is poor, and the magnetic permeability of Comparative Example 2 is low. Therefore, Example 1 achieves excellent insulation and good magnetic permeability values, and the performance meets the design requirements.

[0045] Example 2

[0046] The preparation method of the alloy material comprises the following steps:

[0047] 1. Select FeSiCr alloy powder with a particle size distribution (median particle size) D'50=5 μm. The mass percentage of each component in the alloy powder and the pretreatment are the same as those in Example 1.

[0048] 2. The difference from step 2 of Example 1 is that the sintering oxidation temperature is set to 850°C, the sintering oxidation time is set to 1.5 hours, and the alloy material has a median particle size D50 of 5.14 μm and a Cr2O3 layer thickness T of 130-150 nm. Figure 2 As shown, the thickness of the Cr2O3 layer is measured by scanning electron microscopy. The thickness of the Cr2O3 layer is uniform and flat, with a thickness of 130-150nm. The percentage of the thickness T of the Cr2O3 layer to D50 is in the range of 2.53% to 2.92%.

[0049] 3. The difference from step 3 of embodiment 1 is that the alloy material obtained in step 2 is pressed and then sintered at a sintering temperature of 870° C. for 9 hours.

[0050] 4. The formed magnetic ring was tested, and the test results are shown in Table 2.

[0051] Comparative Example 3

[0052] The difference from Example 2 is that the sintering oxidation time in step 2 is 20 minutes. After scanning electron microscope analysis and measurement, the thickness of the Cr2O3 layer on the surface of the alloy material obtained in Comparative Example 3 is 20-40nm, the median particle size D50 of the alloy material particles is 5.03μm, and the percentage of the thickness T of the Cr2O3 layer to D50 is in the range of 0.40% to 0.80%. The other steps are the same as those in Example 2. The performance test of the magnetic ring formed by the alloy material of Comparative Example 3 is carried out, and the test results are shown in Table 2.

[0053] Comparative Example 4

[0054] The difference from Example 2 is that the sintering oxidation time in step 2 is 5 hours. After scanning electron microscope analysis and measurement, the thickness of the surface Cr2O3 layer of the alloy material obtained in Comparative Example 4 is 210-230nm, the median particle size D50 of the alloy material particles is 5.22μm, and the percentage of the thickness T of the Cr2O3 layer to D50 is in the range of 4.02% to 4.41%. The other steps are the same as in Example 2, and the performance test of the magnetic ring formed by the alloy material of Comparative Example 4 is carried out, and the test results are shown in Table 2.

[0055] Table 2:

[0056] project Magnetic Permeability Insulation(MΩ) Withstand voltage(V) Comparative Example 3 113 410 104 Example 2 104 1969 1008 Comparative Example 4 73 2000 1316

[0057] As can be seen from Table 2, the magnetic permeability of the sample of Example 2 is 104, the withstand voltage reaches 1969V, and the magnetic permeability is close to 87% of the theoretical value (the theoretical value of the magnetic permeability of the material in this example is 120). The sample of Example 2 is closer to the theoretical value under the condition of meeting the insulation withstand voltage requirements, while the insulation withstand voltage of the sample of Comparative Example 3 is poor, and the magnetic permeability of Comparative Example 4 is low. Therefore, Example 2 achieves a good balance between insulation and magnetic permeability, ensuring the stability and withstand voltage performance of the product under working conditions.

[0058] Example 3

[0059] The preparation method of the alloy material comprises the following steps:

[0060] 1. Select FeSiCr alloy powder with a particle size distribution (median particle size) of D'50=10 μm. The mass percentage of each component in the alloy powder and the pretreatment are the same as those in Example 1.

[0061] 2. The difference from step 2 of Example 1 is that the sintering oxidation temperature is set to 850°C, the sintering oxidation time is set to 2 hours, and the median particle size D50 of the alloy material particles is obtained to be 10.50μm, the thickness T of the Cr2O3 layer is 450-550nm, and the percentage of the thickness T of the Cr2O3 layer to D50 is in the range of 4.29% to 5.24%.

[0062] 3. The difference from step 3 of embodiment 1 is that the alloy material obtained in step 2 is pressed and then sintered at a sintering temperature of 870° C. for 9 hours.

[0063] 4. The formed magnetic ring was tested. The test results are shown in Table 3.

[0064] Comparative Example 5

[0065] The difference from Example 3 is that the sintering oxidation time in step 2 is 27 minutes. After scanning electron microscope analysis and measurement, the thickness of the Cr2O3 layer on the surface of the alloy material obtained in Comparative Example 5 is 150-250nm, the median particle size D50 of the alloy material particles is 10.20μm, and the percentage of the thickness T of the Cr2O3 layer to D50 is in the range of 1.47% to 2.45%. The other steps are the same as those in Example 3. The performance test of the magnetic ring formed by the alloy material of Comparative Example 5 is carried out, and the test results are shown in Table 3.

[0066] Comparative Example 6

[0067] The difference from Example 3 is that the sintering oxidation time in step 2 is 6 hours. After scanning electron microscope analysis and measurement, the thickness of the surface Cr2O3 layer of the alloy material obtained in Comparative Example 6 is 950-1050nm, the median particle size D50 of the alloy material particles is 11.00μm, and the percentage of the thickness T of the Cr2O3 layer to D50 is in the range of 8.64% to 9.55%. The other steps are the same as those in Example 3. The performance test of the magnetic ring formed by the alloy material of Comparative Example 6 is carried out, and the test results are shown in Table 3.

[0068] Table 3:

[0069] project Magnetic Permeability Insulation(MΩ) Withstand voltage(V) Comparative Example 5 110 271 104 Example 3 99 2000 1734 Comparative Example 6 71 2280 1960

[0070] It can be seen from Table 3 that Example 3 achieves a good balance between insulation and magnetic permeability, ensuring the stability and voltage resistance of the product under working conditions.

[0071] Example 4

[0072] The preparation method of the alloy material comprises the following steps:

[0073] 1. Select FeSiCr alloy powder with a particle size distribution (median particle size) D'50=20 μm. The mass percentage of each component in the alloy powder and the pretreatment are the same as those in Example 1.

[0074] 2. The difference from step 2 of Example 1 is that the sintering oxidation temperature is set to 880°C, the sintering oxidation time is set to 3 hours, and the median particle size D50 of the alloy material particles is obtained to be 21.7μm, the thickness T of the Cr2O3 layer is 1550-1850nm, and the percentage of the thickness T of the Cr2O3 layer to D50 is in the range of 7.14% to 8.53%.

[0075] 3. The difference from step 3 of embodiment 1 is that the alloy material obtained in step 2 is pressed and then sintered at a sintering temperature of 870° C. for 9 hours.

[0076] 4. The formed magnetic ring was tested. The test results are shown in Table 4.

[0077] Comparative Example 7

[0078] The difference from Example 4 is that the sintering oxidation time in step 2 is 25 minutes. After scanning electron microscope analysis and measurement, the thickness of the Cr2O3 layer on the surface of the alloy material obtained in Comparative Example 7 is 300-500nm, the median particle size D50 of the alloy material particles is 20.4μm, and the thickness T of the Cr2O3 layer accounts for a percentage of D50 in the range of 1.47% to 2.45%. The other steps are the same as those in Example 4. The performance test of the magnetic ring formed by the alloy material of Comparative Example 7 is carried out, and the test results are shown in Table 4.

[0079] Comparative Example 8

[0080] The difference from Example 4 is that the sintering oxidation time in step 2 is 6 hours. After scanning electron microscope analysis and measurement, the thickness of the Cr2O3 layer on the surface of the alloy material obtained in Comparative Example 8 is 2400-2700nm, the median particle size D50 of the alloy material particles is 22.5μm, and the percentage of the thickness T of the Cr2O3 layer to D50 is in the range of 10.67% to 12.00%. The other steps are the same as those in Example 4, and the performance test of the magnetic ring formed by the alloy material of Comparative Example 8 is carried out, and the test results are shown in Table 4.

[0081] Table 4:

[0082] project Magnetic Permeability Insulation(MΩ) Withstand voltage(V) Comparative Example 7 117 196 301 Example 4 107 1743 1651 Comparative Example 8 83 1866 1731

[0083] It can be seen from Table 4 that Example 4 achieves a good balance between insulation and magnetic permeability, ensuring the stability and voltage resistance of the product under working conditions.

[0084] The above embodiments optimize the magnetic permeability and insulation withstand voltage of the alloy material by adjusting the thickness of the Cr2O3 layer so as to adjust the proportional relationship between the median particle size D50 of the alloy material particles and the thickness T of the Cr2O3 layer. Therefore, the alloy material of the present invention has a simple preparation process, higher stability, durability and electrical properties, and higher market competitiveness and application value.

[0085] The above content is a further detailed description of the present invention in combination with specific / preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, it can also make several substitutions or modifications to these described embodiments, and these substitutions or modifications should be regarded as belonging to the protection scope of the present invention. In the description of this specification, the description of reference terms "an embodiment", "some embodiments", "preferred embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in combination with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily target the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In the absence of mutual contradiction, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples. Although the embodiments of the present invention and their advantages have been described in detail, it should be understood that various changes, substitutions and modifications can be made herein without departing from the scope of protection of the patent application.

Claims

1. An alloy material for inductance, characterized in that: The particles of the alloy material are of a core-shell structure, wherein the shell is attached to the outer surface of the core, the core is a FeSiCr alloy particle, and the shell is a Cr2O3 layer, wherein the median particle size D50 of the particles of the alloy material and the thickness T of the Cr2O3 layer satisfy the following relationship: when 3μm≤D50<5μm, the percentage of T in D50 is in the range of [0.98%, 2.49%]; when 5μm≤D50<10μm, the percentage of T in D50 is in the range of (2.49%, 3.95%]; when 10μm≤D50<25μm, the percentage of T in D50 is in the range of (3.95%, 8.56%]).

2. The inductor alloy material according to claim 1, characterized in that: When the median particle size D50 of the alloy material particles is 3.04 μm, the percentage of T in D50 is in the range of 0.99% to 1.64%; when the median particle size D50 of the alloy material particles is 5.14 μm, the percentage of T in D50 is in the range of 2.53% to 2.92%; when the median particle size D50 of the alloy material particles is 10.50 μm, the percentage of T in D50 is in the range of 4.29% to 5.24%; when the median particle size D50 of the alloy material particles is 21.7 μm, the percentage of T in D50 is in the range of 7.14% to 8.53%.

3. A method for preparing the alloy material for inductance according to any one of claims 1 to 2, characterized in that: The steps include: (1) Using FeSiCr alloy powder as raw material, cleaning the surface of the powder to remove the naturally oxidized part of the powder surface; (2) In an inert atmosphere containing oxygen, the FeSiCr alloy powder cleaned in step (1) is sintered to form a Cr2O3 layer on the surface of the particles, thereby obtaining the inductor alloy material, wherein the median particle size D50 of the inductor alloy material is in the range of 3 to 25 μm.

4. The preparation method according to claim 3, characterized in that: In step (2), the thickness of the Cr2O3 layer is controlled by controlling at least one of the sintering temperature, the sintering time and the oxygen concentration in the inert atmosphere, thereby controlling the proportional relationship between the median particle size D50 of the alloy material particles and the thickness T of the Cr2O3 layer.

5. The preparation method according to claim 4, characterized in that: In step (2), the sintering temperature is 750-880° C., the sintering time is 0.5-3 h, and the oxygen concentration in the inert atmosphere is 21 vol% to 50 vol%.

6. The preparation method according to claim 3, characterized in that: The Cr content in the FeSiCr alloy powder in step (1) is ≥2wt%; preferably, in step (1), the Cr content in the FeSiCr alloy powder is ≥2wt% and ≤4wt%.

7. The preparation method according to claim 3, characterized in that: The FeSiCr alloy powder in step (1) contains 91.5wt%-93.5wt% of Fe, 4.5wt% of Si and 2.0wt%-4.0wt% of Cr.

8. The preparation method according to claim 7, characterized in that: In step (1), the FeSiCr alloy powder contains 91.5wt% Fe, 4.5wt% Si and 4.0wt% Cr; or the FeSiCr alloy powder contains 92.5wt% Fe, 4.5wt% Si and 3.0wt% Cr; or the FeSiCr alloy powder contains 93.5wt% Fe, 4.5wt% Si and 4.0wt% Cr.

9. The preparation method according to claim 3, characterized in that: The median particle size D'50 of the FeSiCr alloy powder in step (1) is in the range of 2 to 20 μm.

10. An inductor, characterized in that: The invention comprises the alloy material for inductance according to any one of claims 1 to 2.

Citation Information

Patent Citations

  • Multilayer electronic component

    CN104575942A

  • Composite particles, core, and electronic component

    CN113571284A

  • Compound magnetic material and manufacturing method thereof

    JP2009158652A

  • Composite particles and dust core

    JP2021036576A

  • Magnetic Beads, Magnetic Beads Dispersion Liquid, Method Of Manufacturing Magnetic Beads, And Method Of Manufacturing Magnetic Beads Dispersion Liquid

    US20230260683A1

Cited By

  • Alloy material for inductor and preparation method therefor, and inductor

    WO2026145256A1